Olympiade 80. Football a Minsk par Intourist (Intourist, 1979)
Colour photograph of sports centre in Minsk, with green sky; large white logo of the Moscow 1980 Summer Olympics on sky Poster advertising the city of Minsk by Intourist travel agency, ahead of the Moscow 1980 Summer Olympics PO-0436